Bowel preparation for elective procedures in children: a systematic review and meta-analysis. Issue 1 (18th September 2017) - Gordon, Morris; Karlsen, Fiona; Isaji, Sahira; Teck, Guan-Ong
Abstract : Objective: Reviews have investigated preparation for colonoscopy, but not for surgery, They are also often limited to patients up to 16 years, despite many paediatric gastroenterologists caring for older patients. We carried out a systematic review investigating the optimum bowel preparation agents for all indications in children and young people. Design: A Cochrane format systematic review of randomised controlled trials (RCTs). Data extraction and assessment of methodological quality were performed independently by two reviewers. Methodological quality was assessed using the Cochrane risk of bias tool. Patients: Young people requiring bowel preparation for any elective procedure, as defined by the primary studies. Interventions: RCTs comparing bowel preparation with placebo or other interventions. Main outcome measures: Adequacy of bowel preparation, tolerability and adverse events. Results: The search yielded 2124 results and 15 randomised controlled studies (n=1435)but heterogeneity limited synthesis. Meta-analysis of two studies comparing polyethylene glycol (PEG) with sodium phosphate showed no difference in the quality of bowel preparation (risk ratio (RR) 1.27(95% CI 0.66 to 2.44)). Two studies comparing sodium picosulfate/magnesium citrate with PEG found no difference in bowel preparation but significantly higher number of patients needing nasogastric tube insertion in the polyethylene glycol-electrolyte lavage solution (RR 0.04(95% CI 0.01 to 0.18), 45 of 117 in PEG group vs 2 of 121 in sodium picosulfate group). Meta-analysis of three studies (n=241) found no difference between PEG and sennasoids (RR 0.73(95% CI 0.31 to 1.71)). Conclusions: The evidence base is clinically heterogeneous and methodologically at risk of bias. There is evidence that all regimens are equally effective. However, sodium picosulfate was better tolerated than PEG. Future research is needed with all agents and should seek to consider safety and tolerability as well as efficacy.